Проблеми планування соціального розвитку підприємства в умовах трансформації ринкових відносин в Україні - Норкіна, О.М.; Смутко, А.М. (Культура народов Причерноморья, 2014)
У статті наведено теоретичні засади управління соціальним розвитком підприємства, визначено фактори, що формують його соціальне середовище. Проаналізовано роль соціальної відповідальності, як фактору підвищення ефективності функціонування підприємства. Розглянуто модель інсайдера–аутсайдера, яка враховує ідентичність працівника та передбачає аналіз поведінки персоналу підприємства залежно від двох типів ідентичності, а також аналіз відповідних винагород. В статье приведены теоретические основы управления социальным развитием предприятия, определены факторы, формирующие его социальную среду. Проанализирована роль социальной ответственности. Как фактора повышения эффективности функционирования предприятия. Рассмотрена модель инсайдера–аутсайдера, которая учитывает идентичность работника и предусматривает анализ поведения персонала предприятия в зависимости от двух типов идентичности, а также анализ соответствующих вознаграждений. The article presents the theoretical foundations of social development management of the company, identifies the factors that form its social environment. The role of social responsibility is analyzed as a factor in increasing the efficiency of the enterprise. We formulate the essence of management of social development and identify its priority areas for businesses in transforming market economy in Ukraine. The article focuses on the process of social development planning of the organization. The methods of social planning are exemplified, and the tasks that are solved by it (i.e. increased productivity, workplace organization, improving wages, quality assurance of work and production) are characterized. Considered a model of insider–outsider, which takes into account the identity of an employee and provides analysis of the staff behavior according to the two types of identities, and also analyses of existing rewards.